PENYULUHAN PENYAKIT INFEKSI KECACINGAN DAN GIARDIASIS TERHADAP ANAK BALITA STUNTING DI KELURAHAN KAMPUNG BARU NAN XX KECAMATAN LUBUK BEGALUNG KOTA PADANG - Adrial Adrial; Nuzulia Irawati; Hasmiwati Hasmiwati; Nurhayati Nurhayati; Selfi Renita Rusjdi; Eka Nofita; Husnil Wardiyah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2024)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition and chronic infections, including worm infections and giardiasis. Kampung Baru Nan XX Village, Lubuk Begalung District, Padang City, is one of the areas with a high stunting rate. Education related to the prevention and treatment of this infectious disease is needed to improve public understanding in order to break the chain of causes of stunting. This counseling activity aims to improve public knowledge, especially mothers of toddlers, about the relationship between worm infections and giardiasis with stunting and preventive measures. The methods used are interactive lectures and discussions. The counseling involved mothers of toddlers and integrated health post cadres in the area. From the examination of 20 feces samples of toddlers in this area, no positive cases of worm infections and giardiasis were found. The results of this activity showed a good understanding of the participants regarding the importance of environmental sanitation, personal hygiene, and providing nutritious food to children. This counseling is effective in increasing public awareness regarding worm infections and giardiasis as risk factors for stunting. Follow-up activities can be carried out in the form of monitoring and providing nutritional interventions to support sustainable stunting prevention in this region.